Analysing the possibility of using a hydraulic transmission with motor wheels for the nomad at off-roader - Avrunin, Grygoriy; Podrigalo, Mikhail; Podrigalo, Nadia; Moroz, Irina; Potoroka, Anatoly; Аврунін, Григорій Аврамович; Подригало, Михайло Абович; Подригало, Надiя Михайлівна; Мороз, Ірина Іванівна; Поторока, Анатолій Владиславович (Харківський національний автомобільно-дорожній університет, 2024)
Problem. The creation of transport vehicles for operation in difficult road conditions requires solving a complex of problems related to the fulfilment of the necessary requirements for speed and traction characteristics, in particular, shifting modes, overcoming climbs, manoeuvrability and increased speed with its stepless change, anti-skid properties. Such requirements are achieved thanks to constructive solutions in transmissions of various types. Goal. The aim is an attempt to create a full-flow continuously variable transmission with hydrostatic transmission and motor-wheels instead of a step-mechanical one to improve the technical characteristics of the all-terrain vehicle and the technological possibilities of manufacturing the transmission by the block method when using standard components. Methodology. Based on the analysis of the technical characteristics of the analogue all-terrain vehicle with a mechanical multi-gear transmission and a review of achievements in modern hydrostatic transmission with hydraulic motor-wheels, static calculations were carried out to assess the possibility of creating a stepless full-flow hydro volume transmission and building its hydraulic schematic diagram. Calculations are based on mathematical models created on the basis of the laws of mechanics and hydraulics. The results. According to the results of the calculations, it has been shown that it is fundamentally possible to create a stepless hydrostatic transmission for an all-terrain vehicle with the specified traction and speed characteristics. Further research is proposed on the analysis of the dynamics of the hydrostatic transmission of the all-terrain vehicle and the creation of a corresponding experimental model of the vehicle. Originality. For the analogue all-terrain vehicle, the hydraulic motor-wheels required for the working volume were selected, which provide the parameters of traction and speed characteristics and allow creating an original transmission without the use of reducers and gearboxes. Practical meaning. The obtained results are planned to be considered as recommended for carrying out a functional and cost analysis in the design and determination of technological possibilities in the manufacture of a hydrostatic transmission of an all-terrain vehicle. It is also proposed to consider the method of calculating the hydrostatic transmission of an all-terrain vehicle in the educational process for master's students of industrial mechanical engineering when studying the disciplines related to the design of hydraulic drives and their tests.
Аналіз можливості застосування гідравлічної трансмісії з мотор-колесами для всюдихода NOMAD ATV
Keywords: all-terrain vehicle; transmissions of off-road vehicles; hydrostatic motor-wheels and pumps; traction-speed characteristics; transmission calculation; всюдихід; трансмісії позашляхових машин; об’ємні гідромотор-колеса та насоси; тягово-швидкісна характеристика; розрахунок трансмісії; 629.225; 10.30977/AT.2219-8342.2024.54.0.02